2014
DOI: 10.1084/jem.20131377
|View full text |Cite
|
Sign up to set email alerts
|

T cell–derived interleukin (IL)-21 promotes brain injury following stroke in mice

Abstract: IL-21 is a key CD4+ T cell–derived inflammatory factor that contributes to increased early ischemic tissue injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
84
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(91 citation statements)
references
References 30 publications
(41 reference statements)
0
84
0
2
Order By: Relevance
“…4&7). Such inhibition of IL-21 could indeed be beneficial to stroke outcome as indicated in a recent report showing that T-cell production of this cytokine can induce brain injury after MCAO (Clarkson et al 2014). Additional regulatory effects observed included reduced expression of MHCII, TNF-α and IL-1β by splenic CD11b + monocytes and enhanced expression of IL-4, IL-10 and IL-33, but reduced expression of ICAM-1, CXCL10, CXCR3 and MMP-9 in the ischemic brain hemisphere (Figs.…”
Section: Discussionmentioning
confidence: 95%
“…4&7). Such inhibition of IL-21 could indeed be beneficial to stroke outcome as indicated in a recent report showing that T-cell production of this cytokine can induce brain injury after MCAO (Clarkson et al 2014). Additional regulatory effects observed included reduced expression of MHCII, TNF-α and IL-1β by splenic CD11b + monocytes and enhanced expression of IL-4, IL-10 and IL-33, but reduced expression of ICAM-1, CXCL10, CXCR3 and MMP-9 in the ischemic brain hemisphere (Figs.…”
Section: Discussionmentioning
confidence: 95%
“…Contrastingly IL-21 is thought to play a key role in inflammatory conditions such as diabetes, multiple sclerosis, Sjogren’s syndrome and brain injury after stroke (4650). Previously we showed that IL-21 production in chronic infection is driven by gp130 signaling (20).…”
Section: Discussionmentioning
confidence: 99%
“…In stroke, the use of strategies aiming to block IL-17 differentiation and maintenance, such as IL-21 68 and IL-23 69,70 as well IL-17 itself, 69,71 led to protective effects. This pathogenic effect of IL-17 could be achieved through interaction of IL-17 with IL-17Rs on astrocytes, microglia, and neurons that activates many transcriptional factors, such as NF-κB, which then induces the expression of proinflammatory cytokines (eg, IL-6, TNFα, and IL-1β), chemokines (eg, CXCL1, CCL2, CXCL2, CCL7, CCL11, and CCL20), and metalloproteinases that facilitate trafficking of leukocytes across the vascular endothelial barrier and their entry into the parenchyma (for review, see Ref.…”
Section: Role Of Il-17 In Postischemic Injurymentioning
confidence: 99%